The kinetics of milk gel structure formation studies by electron microscopy - I. T. Smykov (Пищевые системы)
The aim of this study is to enhance the comprehension of the mechanism of enzymatic gelation in milk by visualizing the evolution of its microstructure through transmission electron microscopy. In order to minimize the potential for artifacts during the preparation process and eliminate any possible difficulties in interpreting the resulting images, three distinct methods were employed in the research: shading the surface topography with vacuum deposition of heavy metal, negative staining of the specimen with a heavy metal solution and replicating a cleavage of a quick-frozen sample. The selection of time intervals for sampling the gel during its evolution is determined by the most probable significant modifications in the resulting gel. Based on the research, it has been shown that natural milk is a nonequilibrium system from the perspective of statistical thermodynamics. A notable observation is that the glycomacropeptides forming the hair layer on the surface of casein micelles are unevenly distributed, leading to the formation of micelle dimers and trimers. It has been determind that during the initial stage of enzymatic gelation in milk, clusters of loosely bound micelles are formed in areas with the highest concentration. The formation of micelle chains is absent at this stage due to the non-anisometric nature of micelles and the energetic disadvantage of their formation. It has been found that under the influence of enzymatic gelation near the gel point, a hierarchical process involving the transformation of the milk’s protein component is activated. The trigger mechanism for this process is a cooperative conformational transition in clusters of casein micelles, which initiates a chain of more energy-intensive reactions in the following sequence: hydrophobic interactions → hydrogen bridges → electrostatic interactions → calcium bridges. The result is the conversion of loosely bound micelle clusters into denser aggregates, predominantly contributing to the formation of milk curd. It is worth noting that gelation in milk can be regarded as a process that reduces the free energy of the dispersed system. Understanding the correlation between the decrease in the free energy value during gelation and the physical properties of the finished cheese and other dairy products continues to be a relevant area of research.